Impact of Renal Failure on F18-FDG PET/CT Scans - Kode, Vishwajit; Karsch, Holly; Osman, Medhat M.; Muzaffar, Razi (Frontiers in Oncology, 2017)
Objective The current guidelines for 2-deoxy-2-[18F]fluoro-d-glucose PET/CT scanning do not address potential inaccuracies that may arise due to patients with renal failure. We report a retrospective analysis of standard uptake values (SUVs) in patients with and without renal failure in order to warrant a protocol adjustment. Methods Patients were matched based on age, gender, and BMI all of which are potential effectors on observed SUV. Thirty patients were selected with clinically diagnosed renal failure, of which 12 were on dialysis. All 30 patients had age, gender, and BMI control matches. Blood urea nitrogen and creatinine levels were measured within 1 month of the scan to assess renal failure. PET/CT scans for both the renal failure patients and controls were performed 60 min after FDG injection. SUVs were measured by placing circular regions of interest in the right hepatic lobe (LSUV) and left psoas muscle (PSUV). Results For the 30 renal failure patients, the mean LSUV was 2.77 (SD = 0.57) and PSUV was 1.43 (SD = 0.30) while the controls had mean LSUV 2.74 (SD = 0.50) and PSUV 1.42 (SD = 0.37). The SUVs from both the liver and psoas muscle were not significantly different between the renal failure patients and the normal controls with p values >0.05. In addition, dialysis and gender also had no effect on SUVs. Conclusion Our data suggest that renal failure patients do not require an adjustment in protocol and the standard protocol times should remain.